Of unbiased beans and slanted stocks: Neutral stimuli reveal the fundamental relation between political ideology and exploratory behaviour. (8th June 2020) - Ruisch, Benjamin C.; Shook, Natalie J.; Fazio, Russell H.
Abstract : Fiagbenu et al . (2019, British Journal of Psychology ) questioned the nature and extent of ideological differences in learning and behaviour documented by Shook and Fazio (2009, Journal of Experimental Social Psychology, 45, 995). We correct a mischaracterization in their depiction of Shook & Fazio's research, and in doing so, we outline why the original findings represent domain‐general ideological differences in attitude‐formation processes, rather than simple differences in responses to physical threat. We also report new data that suggest a potential mechanism for the authors' findings and further highlight the importance of novel, ideologically neutral stimuli when examining fundamental psychological differences between liberals and conservatives.